Economic Inequality in Coastal Area of Bengkulu Province - Nola Windirah; Muhamad Mustopa Romdhon; Satria Putra Utama; Reflis (Talenta Publisher, 2020)
The issue of economic inequality is still a major issue in development in the coastal areas of Bengkulu Province. The region's high economic growth (5.3%) was eroded by the high rate of inflation (5%), the economy grew only 0.3 - 0.5%. The question is whether the decreasing of Bengkulu Province's economic growth due to inflation has contributed to regional economic inequality, on the coast of Bengkulu Province specifically ? The data analysis method used to assess the level of economic inequality is the Williamson Index. The results indicated that the economic growth (Gross Regional Domestic Product - GRDP) in coastal areas was lower than in non-coastal areas. Economic disparities between coastal and non-coastal areas in Bengkulu Province for the 2010-2013 period widened, however inequality in coastal areas was smaller than in non-coastal areas.